Empowering Respectful and Inclusive Placement Experiences - Laura Burge; Alicea Yu; Rhiannon Tanner; Thanura Ediri; Alisha Stewart; Mary Rabahi (JANZSSA)
Research from the Australian Human Rights Commission (2017) and the National Student Safety Survey (Heywood et al., 2022) revealed the prevalence of sexual harm experienced by students during internships and placements, with perpetrators often being colleagues and clients outside the university. The Action Plan Addressing Gender-Based Violence in Higher Education (Department of Education, 2024a) identifies placements as high-risk environments, prompting action to address this issue. Over several years, Deakin University’s sexual harm prevention and response teams have partnered with Work Integrated Learning staff to enhance awareness of support and report services. This has included the implementation of a university-wide module to educate students on their rights, responsibilities, and personal safety during internships and placements. This paper provides an overview of the design, development, and initial launch of the module with discussion of future directions.